Profitabilitas : Dampak dari Likuiditas dan Leverage Keuangan - Dede Hertina; Mohamad Bayu Herdiawan Hidayat; Dewi Putri Damayanti (Jurnal Ekonomi Manajemen Perbankan, 2019)
The purpose of this study is to determine the liquidity and financial leverage effect on profitability. The object of this research was carried out at various industrial manufacturing companies in the automotive sub-sector and components listed on the Indonesia Stock Exchange for the period 2012-2017 which were measured using the Current Ratio, the Return to Assets. The sampling method in this study uses purposive sampling with panel data regression analysis so that there are 12 companies that fit the criteria of the sample. The results of testing hypotheses together show liquidity and financial leverage affect profitability, while partially, only liquidity has an influence on profitability, financial leverage variable does not affect the profitability of the company